Prevalence and etiological agents for chronic suppurative otitis media in a tertiary hospital in Tanzania - Zephania Saitabau Abraham; Daudi Ntunaguzi; Aveline Aloyce Kahinga; Kassim Babu Mapondella; Enica Richard Massawe; Emmanuel James Nkuwi; Aslam Nkya (BMC Research Notes, 2019)
Abstract Objective Chronic suppurative otitis media is among the most common otological condition reported in otorhinolaryngology practice commonly attributing to preventable hearing loss. The aim of this study was to determine the prevalence and etiological agents for chronic suppurative otitis media in our department. Results A total of 5591 patients were recruited in this study and only 79 (1.4%) had chronic suppurative otitis media. A male preponderance 43 (54.4%) was noted in this study and the left ear (58.2%) was more commonly affected compared to the right ear. Central perforation was the commonest pattern of presentation and was reported in 53% of cases though none had attic perforation. Of the 81 processed ear swabs, microbial growth was seen in majority 80 (98.8%) whilst one sample showed no microbial growth whereas 52.5% had polymicrobial growth. Among the isolates, most were gram negative species accounting for 59.7% while gram positive bacteria accounted for 25.6% and fungi accounted for 14.7%. Most of these isolates were facultative anaerobes. Klebsiella pneumoniae (20.2%) was the commonest isolates while Escherichia coli and Pseudomonas aeruginosa were equally least isolated (10.9%). Tested isolates were most sensitive to Ciprofloxacin, Gentamycin, Ceftriaxone and Amikacin and least sensitive to Amoxicillin/clavulanic acid and Ampicillin.